Artificial intelligence in supply chains - Zapke, Martin (2019)
Artificial Intelligence (AI) is set to drive a new wave of digital disruption that redefines industries and propels unprecedented levels of innovation. As one of the most data-rich environments within companies, supply chains create significant opportunities to harness the benefits of AI. This study follows a qualitative research approach that aims to explore the impacts and applications of AI within the supply chain. It was found that AI creates a broad spectrum of use cases that drive efficiency, automation and customer-centricity across all components of the end-to-end supply chain.